Analisis Fungsi, Kategori, dan Peran Sintaksis Sebagai Kalimat Efektif dalam Teks Cerita Anak “Berbeda Itu Tak Apa” Buku Ajar Bahasa Indonesia Siswa Kelas I SD Negeri 050611 Aman Damai - Nurul Arfika; Ade Hermansyah Pohan; Elly Prihasti Wuriyani; Wisman Hadi (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Children's story texts are events based on the time sequence experienced or in the form of imagination that tells the world of children. This story text is able to improve children's language skills through reading. The children's story text entitled